(untitled) (Latakia University Journal -Basic Sciences Series, 2021)
The importance of this study stems from the fact that it studied a type of localization related to marbled lime of economic importance which aimed to carry out a geological study of carbonate rocks in the Badrosiyah region, to determine the petrographic and sedimentary features, sedimentation environments and petrophysical properties such as impregnation rate to determine the economic quality of the samples, To this destination, has been done 3 field tours were conducted for the study site (Front 6), and been preparing 10 slides. The petrological study showed that the existing rocks are of limestone exposed to the Dalmatiation process (semi-marble), which increased its hardness. And the aviolite rocks caused pressure on those rocks that gave heat helped the Dalmatiation occur. The petrophysical study showed low porosity and variation in the levels of impregnation between the samples taken, which indicates the hope layer containing the investment able rocks according to the Syrian standard specifications, it is a limestone dolomite layer a dumplings light tahini color. By comparing the results of petrological, and petrophysical study of a range containing group of samples, It is found that the quality of these samples is matched for use as building material.